1998
DOI: 10.1063/1.367338
|View full text |Cite
|
Sign up to set email alerts
|

Transport and structural modification during nitrogen implantation of hard amorphous carbon films

Abstract: Hard amorphous carbon (ta-C) films were implanted with 20 keV N+ ions with different fluences up to 6×1017/cm2 at different substrate temperatures. The nitrogen content of the films was monitored in situ using elastic recoil detection analysis. A characteristic temperature dependence is observed for the maximum achievable [N]/[C] composition ratio, with a drop of the saturation level from the room-temperature value of 0.35 to 0.17–0.12 above 150 °C. It is shown that the higher nitrogen retention at room temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…We found that the nitrogen incorporation into a-C films decreases at higher deposition temperature, as also observed by other groups. 14,44,45 Recently it was also found that the nitrogen etch rate of ta-C decreases with increasing temperature. 46 This was explained by physisorbtion of N 2 at the growing film surface and then ion impingement would release CN and N into the gas phase.…”
Section: A Deposition Processesmentioning
confidence: 98%
“…We found that the nitrogen incorporation into a-C films decreases at higher deposition temperature, as also observed by other groups. 14,44,45 Recently it was also found that the nitrogen etch rate of ta-C decreases with increasing temperature. 46 This was explained by physisorbtion of N 2 at the growing film surface and then ion impingement would release CN and N into the gas phase.…”
Section: A Deposition Processesmentioning
confidence: 98%
“…TRIM.SP predicts the correct magnitude and energy dependence. 4,5,11,15,19,20 In conclusion, particle-beam experiments in an ultrahigh vacuum chamber ͑MAJESTIX experiment͒ show that bombardment of a-C : H layers with N 2 + causes chemical sputtering. In contrast to the shown Ne results and our other experiments with noble gas ions, the yields calculated with TRIM.SP significantly underestimate the N 2 + erosion yields and predict a pronounced energy dependence.…”
mentioning
confidence: 92%
“…14,15 A common observation in plasma-deposition experiments is that the deposition rate decreases with increasing nitrogen addition to the working gas and that the maximal achievable nitrogen fraction in the material is limited to about 30 to 40 at. 4,5,11,15,19,20 Chemical sputtering proceeds via formation of volatile HCN, CN, and C 2 N 2 . 2,16 Some authors speculated that this is due to the formation of volatile CN species during the interaction of energetic nitrogen ions with the carbon surface.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Various deposition techniques have been adopted. They include dc and rf magnetron sputtering deposition, [5][6][7][8][9] ion beam and ion beam assisted deposition, 10-12 nitrogen implantation, 13 pulsed laser deposition, [14][15][16][17][18] and chemical vapor deposition. [19][20][21] Recently, we have prepared crystalline carbon nitride thin films with a high nitrogen content by the electron cyclotron resonance ͑ECR͒ sputtering deposition.…”
Section: Introductionmentioning
confidence: 99%